To simplify the expression \( \frac{1}{4} - 0.5 + \frac{1}{2} - 0.25 + \frac{3}{5} + 0.4 \), we will convert all numbers to fractions with a common denominator.
First, let's convert the decimal numbers to fractions:
- \( 0.5 = \frac{1}{2} \)
- \( 0.25 = \frac{1}{4} \)
- \( 0.4 = \frac{2}{5} \)
Now, the expression looks like this:
\[ \frac{1}{4} - \frac{1}{2} + \frac{1}{2} - \frac{1}{4} + \frac{3}{5} + \frac{2}{5} \]
Next, let's combine the terms:
-
Combine \( \frac{1}{4} \) and \( -\frac{1}{4} \): \[ \frac{1}{4} - \frac{1}{4} = 0 \]
-
Combine \( -\frac{1}{2} \) and \( \frac{1}{2} \): \[ -\frac{1}{2} + \frac{1}{2} = 0 \]
Now the expression simplifies to:
\[ 0 + 0 + \frac{3}{5} + \frac{2}{5} \]
Combine \( \frac{3}{5} \) and \( \frac{2}{5} \):
\[ \frac{3}{5} + \frac{2}{5} = \frac{5}{5} = 1 \]
Therefore, the value of the original expression is:
\[ \boxed{1} \]